AggR, a transcriptional activator of aggregative adherence fimbria I expression in enteroaggregative Escherichia coli. - Nataro, J P (1994)
Enteroaggregative Escherichia coli (EAggEC) has been associated with persistent pediatric diarrhea in the developing world, yet the pathogenetic mechanisms of EAggEC infection are unknown. Our previous data have suggested that aggregative adherence of some EAggEC strains to HEp-2 cells is mediated by flexible, bundle-forming fimbriae, which we have termed aggregative adherence fimbriae I (AAF/I). Genes sufficient to confer expression of AAF/I are located on the 60-MDa plasmid of EAggEC 17-2; AAF/I genes are present as two unlinked plasmid regions (regions 1 and 2), separated by 9 kb of DNA. Here we report the complete DNA sequencing of region 2 and the identification of an open reading frame which is involved in the expression of AAF/I. One open reading frame of 794 bp encodes a protein (designated AggR) with a predicted molecular size of 29.4 kDa, which shows a high degree of amino acid sequence identity to CfaR and other members of the AraC class of gene regulators. The cloned aggR gene (or, alternatively, a cloned cfaR gene) was sufficient to complement a region 1 clone to confer AAF/I expression. To further substantiate the role of aggR in the regulation of AAF/I, we constructed a 289-bp in-frame aggR deletion and replaced the native gene in 17-2 by allelic exchange, using the temperature-sensitive vector pIB307. The resulting aggR deletions were negative for AAF/I expression, but expression was restored when the aggR gene (cloned into pBluescript II SK) was reintroduced into the aggR mutant. RNA slot blot experiments using a probe for the putative AAF/I pilin subunit (aggA) revealed that aggR operates as a transcriptional activator of aggA expression. aggA::phoA fusions were constructed in 17-2 and in 17-2 delta aggR. AggR was found to promote expression of the aggA gene under a variety of conditions of temperature, osmolarity, oxygen tension, and medium. At acid pH, aggA expression was maximal and was regulated by both AggR-dependent and AggR-independent mechanisms.